Sensibility and sense of belonging to the place in promoting the social capital of the villagers (Case study: Kurdish villages, Rudbar city) - Majid Yasouri; Samira Mahmoudi; Ali Reza Darban Astaneh; Fatemeh Emami (تحقیقات کاربردی علوم جغرافیایی)
Social capital plays an important role in increasing bioavailability, which undoubtedly is the main goal of all planning and development, including rural planning and development. This research is an applied and descriptive-analytical approach that is conducted with a sample of 355 people among the people of Kurdish villages in Rudbar city. The data gathering tool in this research included: library studies for gathering information about research literature and then field research through observation and questionnaire. The statistical population of the study is Kurdish villages of Guilan province in Rudbar with 12 villages and 2955 population (according to the census of 1395). The number of samples was determined using the Morgan table, 340 people were selected. To increase the level of confidence and reduce the error in the data, the number of samples was increased and 355 questionnaires were completed The research was used to systematically explain the factors influencing location and achieve a comprehensive model of multivariate path analysis. The direct and indirect effects of the variables discussed were studied in a model. The results of the research indicate that the physical variables of spatial belonging (0.445), the dimension of social capital trust (0.126), the environmental dimension of spatial attachment (0.168), spatial sense of belonging dimension (0.99), social correlation dimension And then social capital participation is the most important factors that directly affect the location of the villagers' affiliation.